2015
DOI: 10.1589/jpts.27.1299
|View full text |Cite
|
Sign up to set email alerts
|

Does restriction of glenohumeral horizontal adduction reflect posterior capsule thickening of the throwing shoulder?

Abstract: Abstract.[Purpose] Glenohumeral posterior capsule tightness possibly relates to posterior capsule thickness (PCT). The purpose of the current study was to analyze the relationships between PCT and glenohumeral range of motion (ROM) in horizontal adduction (HAdd) and internal rotation (IR). [Subjects and Methods] This study recruited 39 healthy collegiate baseball players. We measured PCT by using ultrasonography and ROM of the glenohumeral joint of the throwing shoulder by using a digital inclinometer. Pearso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 18 publications
1
14
0
1
Order By: Relevance
“…For glenohumeral IR, arthroscopic findings have demonstrated that athletes with glenohumeral IR deficits show contracted and thickened posterior capsules [15]. Furthermore, our ultrasonographic study also reported a significant relationship between increased posterior capsular thickness and glenohumeral IR deficits [16]. Another study also showed that stiffness of the posterior capsule was associated with loss of glenohumeral IR [18].…”
Section: Supraspinatus Tendon Changes and Glenohumeral Range Of Motion In College Baseball Playerssupporting
confidence: 63%
See 3 more Smart Citations
“…For glenohumeral IR, arthroscopic findings have demonstrated that athletes with glenohumeral IR deficits show contracted and thickened posterior capsules [15]. Furthermore, our ultrasonographic study also reported a significant relationship between increased posterior capsular thickness and glenohumeral IR deficits [16]. Another study also showed that stiffness of the posterior capsule was associated with loss of glenohumeral IR [18].…”
Section: Supraspinatus Tendon Changes and Glenohumeral Range Of Motion In College Baseball Playerssupporting
confidence: 63%
“…Prior studies implicated the posterior region of the deltoid and the infraspinatus in the loss of HAd [17,27]. Instead, posterior capsule tightness is thought to mainly affect glenohumeral IR deficit [16,18], resulting in the risk of rotator cuff tendon injuries with internal impingement. Considering the fact that there were relationships between loss of glenohumeral HAd and throwing-shoulder injuries in a prior study [5], the current results suggest that loss of HAd may be associated with other throwing shoulder injuries such as labral tears and biceps tendon injuries.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Several researchers have tested shoulder horizontal adduction (SHA) to measure PST 14 , 15 , 16 , 17 , 18 ) . Warner et al 18 ) used a goniometer to measure SHA of subjects in the supine position.…”
Section: Introductionmentioning
confidence: 99%